Pengaruh Online Customer Review dan Rating terhadap Minat Beli pada Aplikasi Pemesanan Hotel Traveloka - Raden Faris Fathin; Heppy Millanyani (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to determine consumer perceptions of online customer reviews and ratings on the Traveloka hotel booking application and to analyze the effect of online customer reviews and ratings on buying interest in the Traveloka hotel booking application. This study uses a quantitative method, by distributing questionnaires to 400 followers of the @explorebandung Instagram account using a purposive sampling technique with criteria for followers of the @explorebandung Instagram account who have made hotel reservations through Traveloka. The primary data used in this study is the result of questionnaire research from respondents while the secondary data is a reference source from previous research and online data that is relevant to the study. The analytical technique used in this research is descriptive analysis, multiple linear regression analysis, analysis of the coefficient of determination using the SPSS 26.0 application. The results showed that there was an influence between online consumer review and rating on buying interest which was tested by testing the hypothesis. Furthermore, online consumer reviews and ratings are able to influence the buying interest variable by 37.7% while the remaining 62.3% is influenced by other factors not examined in this study. Keywords: Online Customer Review and Rating, Buying Interest, Traveloka